2001
DOI: 10.1007/s001340100875
|View full text |Cite
|
Sign up to set email alerts
|

Antagonization of TNF attenuates systemic hemodynamic manifestations of envenomation in a rat model of Vipera aspis snakebite

Abstract: The hemodynamic consequences of intramuscular injection of V. aspis venom can be blunted in a rat by systemic antagonization of TNF activity prior to venom injection. The poisonous hemodynamic effects of the V. aspis venom might be caused by systemic release of TNF.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2001
2001
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(4 citation statements)
references
References 0 publications
0
4
0
Order By: Relevance
“…Venom-treated cells also produced very high NO levels, as one would expect from the presence of cytokines able to induce iNOS. Venom from the asp, Vipera aspis, increases serum TNF levels in rats (390); either anti-TNF antibody or soluble TNF receptor (p55), when injected at the same time as the venom, prevented certain harmful changes (389). Further study by this group has demonstrated that TNF is the cause of deleterious cardiac effects induced by this venom, in that anti-TNF antibody prevented these changes (388).…”
Section: Pathology Caused By Snake Venommentioning
confidence: 99%
“…Venom-treated cells also produced very high NO levels, as one would expect from the presence of cytokines able to induce iNOS. Venom from the asp, Vipera aspis, increases serum TNF levels in rats (390); either anti-TNF antibody or soluble TNF receptor (p55), when injected at the same time as the venom, prevented certain harmful changes (389). Further study by this group has demonstrated that TNF is the cause of deleterious cardiac effects induced by this venom, in that anti-TNF antibody prevented these changes (388).…”
Section: Pathology Caused By Snake Venommentioning
confidence: 99%
“…Another rat study in 2000 reported by Petricevich et al 15 showed that B. asper and Bothrops jararaca venom that was given intraperitoneally increased TNFα and IL-6 levels. Szold et al 16 reported that rats given Vipera apsis venom had increased systemic TNFα and local tissue damage. This study was divided into four groups; group 1 received only venom, group 2 was injected with venom and anti-TNFα antibody, group 3 was injected with venom and soluble TNFα receptor and group 4 was a control group.…”
Section: Discussionmentioning
confidence: 99%
“…Reported to be safe and efficacious in a small clinical trial [97] Autoimmune encephalomyelitis Ameliorated experimental autoimmune encephalomyelitis [98][99][100]; however, failed to show benefits in a Phase II study with lenercept [79] Experimental painful neuropathy Reduced thermal hyperalgesia and allodynia in a mouse model after either topical or systemic administration [101] Spondyloarthropathies Remarkably effective in improving the clinical manifestations of resistant spondyloarthropathy [102,103]; achieved rapid remission in refractory ankylosing spondylitis [103,104] Corneal graft rejection Gene transfer of a receptor increased graft survival [105] Experimental glomerular nephritis Reduced glomerular damage along with decreased infiltration of neutrophils and monocytes in an accelerated rat model [106] Vipera aspis snakebite Blunted haemodynamic changes in a rat model of envenomation [107] Fever and sleepiness Treated hereditary periodic fever and warming-induced sleep responses in rabbits [108,109] LPS: Lipopolysaccharide; sTNFR: Soluble TNF receptor.…”
Section: Diabetesmentioning
confidence: 99%